齿轮传动设计两种计算标准的比较研究 - 周长江; 唐进元; 刘艳萍; 刘江南 (Jixie chuandong)
Comparative study about the calculation of cylindrical gear drive design are processed between the standards of ISO/GB and AGMA,then the specialty of calculating formulas is researched and the meaning and selection of relative fators are investigated.The study indicates:compared with the calculation of ISO/GB,numeric design and frame optimization in gear drive are implemented conveniently with the one of AGMA,but the conclusions from the two calculation of spur gear drive design lean to conservation.